Communication Strategy in Enhancing Business Development for Fish Cracker Craftsmen in Damarsi Village Sidoarjo Regency - Qomariyah, Siti Nur; Falasifah, Nihlatul (Proceedings of International Conference on Da'wa and Communication, 2024)
This research discusses the communication strategies used to organize the fish cracker craftsmen community as an effort to develop businesses in Damarsi Village, Sidoarjo Regency. This research focuses on the communication strategies used in the organization process and the changes after the mentoring process. The research uses the ABCD (Asset-Based Community Development) approach. Changes after mentoring include understanding the basics of product identity creation, recognizing the importance of business legality and obtaining a business identification number, comprehending digital marketing education and training, forming joint business groups, and establishing cooperation with the local village government. This research is part of the da’wah bil hal effort, which involves enjoining good and forbidding evil by providing education and training related to entrepreneurship. These efforts are made to encourage community awareness in making changes. Essentially, Allah will reward those who strive for change.